Test of Larvacide Activity from Some Sponge Extracts to Aedes aegypti Larvae - Efra D. L. Wantah; R. E. P. Mangindaan; Fitje Losung (Sam Ratulangi University, 2018)
Marine organisms have been known produce certain compounds those could lead for medicine purposes. Sponges are one and the most studied for this aim. oneof the important biological activities which expected from sponge are larvacide activity. The aims this research was to test the larvacide activity aagainst Aedes aegypti larvae from some of sponge extract. Sponge samples were taken from Malalayang Waters, (N 01 Â° 27'37